The God delusion - Dawkins, Richard, 1941- (London, UK: Transworld Publishers, 2007)
"A preeminent scientist - and the world's most prominent atheist - asserts the irrationality of belief in God and the grievous harm religion has inflicted on society, from the Crusades to 9/11."--BOOK JACKET.
A deeply religious nonbeliever -- "Respect" -- The God hypothesis -- Polytheism -- Monotheism -- Secularism, the founding fathers and the religion of America -- The poverty of agnosticism -- Noma -- The great prayer experiment -- The Neville Chamberlain school of evolutionists -- Little green men -- Arguments for God's existence -- Thomas Aquinas's "proofs" -- The ontological argument and other a priori arguments -- The argument from beauty -- The argument from personal "experience" -- The argument from Scripture -- The argument from admired role models -- Pascal's Wager -- Bayesian arguments -- Why there almost certainly is no God -- The ultimate Boeing 747 -- Natural selection as a consciousness-raiser -- Irreducible complexity -- The worship of gaps -- The anthropic principle : planetary version -- The anthropic principle : cosmological version -- An interlude at Cambridge -- The roots of religion -- The Darwinian imperative -- Direct advantages of religion -- Group selection -- Religion as a byproduct of something else -- Psychologically primed for religion -- Tread softly, because you tread on my memes -- Cargo cults -- The roots of morality : why are we good? -- Does our moral sense have a Darwinian origin? -- A case study in the roots of morality -- If there is no God, why be good? -- The "good" book and the changing moral Zeitgeist -- The Old Testament -- Is the New Testament any better? -- Love thy neighbour -- The moral Zeitgeist -- What about Hitler and Stalin? : weren't they atheists? -- What's wrong with religion? : why be so hostile? -- Fundamentalism and the subversion of science -- The dark side of absolutism -- Faith and homosexuality -- Faith and the sanctity of human life -- The great beethoven fallacy -- How "moderation" in faith fosters fanaticism -- Religion and childhood -- Physical and mental abuse -- In defence of children -- An educational scandal -- Consciousness-raising again -- Religious education as a part of literary culture -- A much needed gap? -- Binker -- Consolation -- Inspiration -- The mother of all Burkas.
Includes bibliographical references (p. [380]-387) and index.
Keywords: Irreligion; Atheism; God; Religion